Rancangan Bangun Sistem Otomatisasi Hidroponik Nutrient Film Technique (NFT) Bayam Hijau berbasis Internet of Things (IoT) - Putra, Novri Erdani; Jaya, Putra (TSAQOFAH, 2025)
This study aims to design and develop an Internet of Things (IoT)-based automation system for Nutrient Film Technique (NFT) hydroponics to cultivate green spinach, offering an innovative solution for efficient, adaptive, and sustainable modern agriculture in the context of urban farming. The research employs a descriptive approach using the Waterfall development model, encompassing stages of analysis, design, implementation, and testing. The system is built using a NodeMCU ESP8266 microcontroller integrated with temperature and humidity sensor (DHT11), pH sensor, TDS sensor, and a water level sensor to monitor the environmental conditions for plant growth. The system automatically activates the water pump when the water level drops below the minimum threshold of 15 mm and also provides manual control via a web dashboard. Testing results demonstrate that all input, processing, and output subsystems function optimally and are well-integrated. Sensor data are displayed in real-time on an LCD and can be remotely accessed through IoT connectivity. The study concludes that the automated NFT system is effective in maintaining optimal growing conditions and has the potential to improve the efficiency and productivity of green spinach cultivation at the household scale. The implication is that this system can serve as a viable smart agriculture technology for urban environments.